POLITENESS STRATEGY USED BY THE ANTAGONIST AND THE PROTAGONIST CHARACTERS IN “THE SILENCE OF THE LAMBS” (A PRAGMATICS STUDY) - Titik Iswati; Sri Minda Murni; I Wayan Dirgeyasa (LINGUISTIK TERAPAN, 2018)
This research dealt with politeness strategy used in the movie The Silence of the Lamb. The aims of this study were (1) to investigate the kinds of politeness strategies used by the antagonist and protagonist characters when they expressed their utterances in the film “The Silence of the Lambs”, (2)  to explain how the strategies used by the two characters, (3) to know the reasons of those characters in employing politeness strategies. The research was conducted by using qualitative design. The source of data of this study was the movie. The data were collected through documentary technique and the instrument was the documentary sheet. The findings of this study revealed that: (1) Based on the categories of politeness strategies proposed by Brown and Levinson, all categories of politeness strategies were found in this film. (2) The bald on record strategy was used for eight times by the antagonist, while the protagonist used it for five times. (3) The use of politeness strategy by the antagonist and protagonist was aimed to perform acts based on J. R. Searle’s theory, namely representatives, directives, commissives and declaration. In addition, new strategies were found in this study. They were self-image building, provoking and influencing. Keywords: Politeness Strategy, Antagonist, Protagonist, Pragmatics